33rd European Congress of the International Union against for Sexually Transmitted Infections (IUSTI-Europe): a Urologist`s Point of View - D. V. Krakhotkin (Вестник урологии, 2020)
The article presents a report of the 33rd European Congress of the International Union against for Sexually Transmitted Infections (IUSTI-Europe) from September 5 to 7, 2019, as well as an advanced course on sexually transmitted infections in the framework of the Congress (IUSTI -Europe advanced course) from September 4 to 5 in Tallinn, Estonia. This article will also highlight some important points about the prevalence, diagnosis and treatment of sexually transmitted infections, as well as the problems of resistance of the main causative agents of STIs to standard therapy, which were voiced by various experts in their presentations, lectures during round tables, plenary sessions and symposia both during the advanced course of IUSTI-Europe, and during the main congress.The study did not have sponsorship. The authors have declared no conflicts of interest.